Rhytidoplasty practices and histological notes for the facial skin of post-bariatric patients - Hugo Leonardo Freire Gomes; Marília Gabriela Xavier Pereira Peixoto; Douglas Vinícius Silva; Roberto Kaluf-Filho; Roberto Kaluf (Revista Brasileira de Cirurgia Plástica, 2019)
Introduction: The number of patients classified as overweight or obese has resulted in an increased number of post-bariatric patients, generating a demand for rhytidoplasty in this public profile. expose the routine and surgical tactics in a teaching hospital, patient profiles, subcutaneous cellular tissue, and the superficial musculoaponeurotic system are compared between post-bariatric and non-post-bariatric patients, as well as histological superficial comparison of the skin. Methods: A review of the data of 32 cases treated in 2012-2016 was conducted in a public hospital in Goiânia-GO. Results: The tactics of rhytidoplasty used in post-bariatric patients do not differ significantly from those used in nonpost- bariatric patients. A histopathological analysis of the collected samples showed marked differences between post-bariatric and non-post-bariatric patients. Conclusion: The surgical technique of rhytidoplasty of post-bariatric patients sustained specific details with satisfactory postoperative surgical results, skin with worse histological quality, perioperative complications within the expected range, and the need for further studies to assess the procedure's durability